2017
DOI: 10.7554/elife.31268
|View full text |Cite
|
Sign up to set email alerts
|

Metformin extends C. elegans lifespan through lysosomal pathway

Abstract: Metformin, a widely used first-line drug for treatment of type 2 diabetes (T2D), has been shown to extend lifespan and delay the onset of age-related diseases. However, its primary locus of action remains unclear. Using a pure in vitro reconstitution system, we demonstrate that metformin acts through the v-ATPase-Ragulator lysosomal pathway to coordinate mTORC1 and AMPK, two hubs governing metabolic programs. We further show in Caenorhabditis elegans that both v-ATPase-mediated TORC1 inhibition and v-ATPase-AX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 46 publications
8
118
0
2
Order By: Relevance
“…Thus, together with experiments involving genetic interactions, AAK-2::GFP expression, and pry-1 and aak-2 transcriptome analysis, the results collectively support the model of PRY-1 and AAK-2 functioning together, potentially forming a complex, to regulate DAF-16 activity for the maintenance of lifespan. It was reported previously that AXL-1, another Axin homolog in C. elegans, interacts with AAK-2 following Metformin treatment, although axl-1 mutants have no age-related phenotypes of their own (Chen et al, 2017). Thus, our work demonstrates that PRY-1 is the sole Axin family member in worms regulating lifespan as well as muscle health.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Thus, together with experiments involving genetic interactions, AAK-2::GFP expression, and pry-1 and aak-2 transcriptome analysis, the results collectively support the model of PRY-1 and AAK-2 functioning together, potentially forming a complex, to regulate DAF-16 activity for the maintenance of lifespan. It was reported previously that AXL-1, another Axin homolog in C. elegans, interacts with AAK-2 following Metformin treatment, although axl-1 mutants have no age-related phenotypes of their own (Chen et al, 2017). Thus, our work demonstrates that PRY-1 is the sole Axin family member in worms regulating lifespan as well as muscle health.…”
Section: Discussionsupporting
confidence: 63%
“…In this study, we report that the C. elegans Axin homolog PRY-1, which is necessary for the embryonic and larval processes, is also essential for the normal lifespan maintenance. Previously, metformin-mediated lifespan extension was shown to depend on another C. elegans Axin-like gene, axl-1, however, axl-1 does not play a role in aging and age-related processes (Chen et al, 2017). We found that animals lacking pry-1 function during adulthood had a shorter lifespan, which was due to deterioration in associated processes as judged by the analysis of age-linked markers.…”
Section: Introductionmentioning
confidence: 56%
“…Metformin, a biguanide used as a first-line drug for treating type 2 diabetes [138], was shown to extend the lifespan of C. elegans [139][140][141], D. melanogaster [142], and mice [143,144]. Moreover, it was shown to delay the onset of age-related diseases, such as cancer, metabolic syndrome [145], and cognitive disorders [146]. Its mechanism of action is associated with the activation of 5 AMP-activated protein kinase (AMPK) [147,148], inhibition of the mammalian target of rapamycin (mTOR) [149], reduction of DNA damage [150,151], and decreased insulin levels and IGF-1 signaling [152][153][154].…”
Section: Metforminmentioning
confidence: 99%
“…Finally, a very recent pathway has been described by Chen et al [140]. The authors showed through genetic manipulation that metformin extends the Caenorhabditis elegans lifespan and attenuates age-related fitness decline via a mechanism that requires v-ATPase-Ragulator-AXIN/LKB1 of the lysosomal pathway [140].…”
Section: Mechanisms Of Metformin Action: a Focus On Molecular Pathwaymentioning
confidence: 99%
“…In toto, the possible molecular mechanisms by which metformin exerts antiageing effects are [13, 91]: (1) inhibition of mitochondrial complex 1 in the electron transport chain and decrease of ROS production [139,141], (2) activation of AMPK [106,124,140,[142][143][144], (3) inhibition of mTOR [106,134,135,140], (4) NF-ĸB inhibition [101], and (5) reduced IGF-1 signalling [145].…”
Section: Mechanisms Of Metformin Action: a Focus On Molecular Pathwaymentioning
confidence: 99%